A global systematic overview of socioeconomic factors associated with antidiabetic medication adherence in individuals with type 2 diabetes - Christian Ming Studer; Marie Linder; Laura Pazzagli (BMC, 2023)
Abstract Background Antidiabetic medication adherence is a key aspect for successful control of type 2 diabetes mellitus (T2DM). This systematic review aims to provide an overview of the associations between socioeconomic factors and antidiabetic medication adherence in individuals with T2DM. Methods A study protocol was established using the PRISMA checklist. A primary literature search was conducted during March 2022, searching PubMed, Embase, Web of Science, as well as WorldCat and the Bielefeld Academic Search Engine. Studies were included if published between 1990 and 2022 and included individuals with T2DM. During primary screening, one reviewer screened titles and abstracts for eligibility, while in the secondary screening, two reviewers worked independently to extract the relevant data from the full-text articles. Results A total of 15,128 studies were found in the primary search, and 102 were finally included in the review. Most studies found were cross-sectional (72) and many investigated multiple socioeconomic factors. Four subcategories of socioeconomic factors were identified: economic (70), social (74), ethnical/racial (19) and geographical (18). The majority of studies found an association with antidiabetic medication adherence for two specific factors, namely individuals' insurance status (10) and ethnicity or race (18). Other important factors were income and education. Conclusions A large heterogeneity between studies was observed, with many studies relying on subjective data from interviewed individuals with a potential for recall bias. Several socioeconomic groups influencing medication adherence were identified, suggesting potential areas of intervention for the improvement of diabetes treatment adherence and individuals' long-term well-being.